2016
DOI: 10.1111/acps.12619
|View full text |Cite
|
Sign up to set email alerts
|

Forty years of structural imaging in psychosis: promises and truth

Abstract: MethodWe present here a critical review of studies involving structural magnetic resonance imaging techniques in psychotic patients published between the 1976-2015 in selected journals of relevance for the field. For each study we extracted summary descriptive variables.Additionally we qualitatively described the main structural findings of each articles in summary notes and we employed a biomarker rating system based on quality of evidence (scored 1-4) and effect size (scored 1-4). Results80 studies meeting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 133 publications
0
31
0
Order By: Relevance
“…For a review on structural MRI measures as predictors of outcome, see Dazzan et al ( 74 ). Outcome prediction based on any of the univariate findings is too inaccurate to be clinically useful ( 75 ). An exception might turn out to be using a lack of elevated dopamine synthesis capacity, which has been associated with antipsychotic treatment resistance in two studies ( 76 , 77 ).…”
Section: Outcome Prediction: Current Evidencementioning
confidence: 99%
“…For a review on structural MRI measures as predictors of outcome, see Dazzan et al ( 74 ). Outcome prediction based on any of the univariate findings is too inaccurate to be clinically useful ( 75 ). An exception might turn out to be using a lack of elevated dopamine synthesis capacity, which has been associated with antipsychotic treatment resistance in two studies ( 76 , 77 ).…”
Section: Outcome Prediction: Current Evidencementioning
confidence: 99%
“…While deficits in working memory have long been proposed as a marker of frontal lobe dysfunction is schizophrenia, an analysis of 30 relevant imaging studies found that half have shown hypofrontality, a few have found no differences, while the remainder noted hyperfrontality [ 28 , 51 ]. A recent meta-analysis of 80 MRI studies of psychoses published between 1976 and 2015 found no diagnostic or prognostic biomarkers [ 52 ]. With regard to depression, a meta-analysis of studies of aberrant brain function during cognitive and emotional processing failed to find any statistically significant evidence of convergence across 59 studies [ 53 ].…”
Section: The Medical Model: Has It Failed Psychiatry?mentioning
confidence: 99%
“…Over recent decades, epidemiological evidence and similarly indirect (“soft”) biological findings indicate that schizophrenia is a disorder of subtle neurodevelopmental abnormality [ 2 , 21 23 ]. However, even the most sophisticated of modern structural and functional neuroimaging techniques applied to young adults with psychotic illness, or even to adolescents showing the putative “at risk mental state”/“attenuated psychosis syndrome”, are unable to resolve hallmarks of abnormal brain development [ 24 , 25 ]. The need is for a “hard” index of brain dysmorphogenesis during embryonic and foetal life that can be accessed readily in individuals throughout their lifespan.…”
Section: Schizophrenia: a Neurodevelopmental Disorder With Facial Dysmentioning
confidence: 99%